2016
DOI: 10.5737/23688076262104111
|View full text |Cite
|
Sign up to set email alerts
|

A mixed method study of a peer support intervention for newly diagnosed primary brain tumour patients

Abstract: Purpose: The purpose of this pilot study was to investigate the impact of an intervention designed to enhance quality of life in newly diagnosed primary brain tumour (PBT) patients. The intervention involved a structured, one time meeting between newly diagnosed PBT patients and trained volunteer "veteran" PBT patients. Methods: Two volunteers met for a single, one-on-one meeting with a total of 10 newly diagnosed PBT patients. A combination of questionnaires and interviews were used to investigate the impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This in turn might be complicated, and to date, no comparison between different centers has been undertaken. However, it is worth noting that studies focusing on the effectiveness of experimental interventions showed promising results in terms of informational needs [47,48], reduced stress, increased hope, and overcoming loneliness [47][48][49][50] in patients with cancer. For example, Schofield [51] compared an intervention, in which formal and informal cares were combined, to care as usual in women with gynecological cancers receiving curative radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…This in turn might be complicated, and to date, no comparison between different centers has been undertaken. However, it is worth noting that studies focusing on the effectiveness of experimental interventions showed promising results in terms of informational needs [47,48], reduced stress, increased hope, and overcoming loneliness [47][48][49][50] in patients with cancer. For example, Schofield [51] compared an intervention, in which formal and informal cares were combined, to care as usual in women with gynecological cancers receiving curative radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The most similar intervention the authors found was the subject of a 2016 mixed methods study by Ozier and Cashman, investigating a single one-to-one meeting between newly diagnosed brain tumour patients and a former brain tumour patient [ 26 ]. Qualitative themes from that study described their intervention as providing a sense of hope, alleviation of loneliness and appreciation of an authoritative source.…”
Section: Discussionmentioning
confidence: 99%